Effect of essential oils of Syzygium aromaticum and Cinnamomum zeylanicum and their major components on biofilm production in Staphylococcus aureus strains isolated from milk of cows with mastitis - Budri, P. E. [UNESP]; Silva, N. C. C. [UNESP]; Bonsaglia, E. C. R. [UNESP]; Fernandes, A. [UNESP]; Araújo, J. P. [UNESP]; Doyama, J. T. [UNESP]; Gonçalves, J. L.; Santos, M. V.; Fitzgerald-Hughes, D.; Rall, V. L. M. [UNESP] (Elsevier B. V., 2015)
Bovine mastitis is an inflammation of the mammary glands of cows and causes significant economic losses in dairy cattle. Staphylococcus aureus is one of the microorganisms most commonly isolated. Novel agents are required in agricultural industries to prevent the development of mastitis. The production of biofilm by Staph. aureus facilitates the adhesion of bacteria to solid surfaces and contributes to the transmission and maintenance of these bacteria. The effect of the essential oils of Syzygium aromaticum (clove; EOSA) and Cinnamomum zeylanicum (cinnamon; EOCZ) and their major components, eugenol and cinnamaldehyde, on Staph. aureus biofilm formation on different surfaces was investigated. The results showed a significant inhibition of biofilm production by EOSA on polystyrene and stainless steel surfaces (69.4 and 63.6%, respectively). However, its major component, eugenol, was less effective on polystyrene and stainless steel (52.8 and 19.6%, respectively). Both EOCZ and its major component, cinnamaldehyde, significantly reduced biofilm formation on polystyrene (74.7 and 69.6%, respectively) and on stainless steel surfaces (45.3 and 44.9%, respectively). These findings suggest that EOSA, EOCZ, and cinnamaldehyde may be considered for applications such as sanitization in the food industry.
Keywords: Cinnamomum zeylanicum; Syzygium aromaticum; Antibiofilm staphylococcus aureus; Mastitis